MENGINISIASI POSYANDU REMAJA DESA KEDUNGAN SEBAGAI UPAYA MENUJU REMAJA SEHAT DAN MEMPERKUAT PENANGULANGAN STUNTING - Indarwati; Tri Susilowati; Annisa Andriani (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Kedungan village government has set a target to reduce the prevalence of stunting from 19% in 2023 to 11% in 2024. Various interventions have been implemented to address stunting, including providing supplementary food for stunted infants and pregnant women. Additionally, Kedungan village, in collaboration with Aisyiyah University of Surakarta, has conducted a community service program to empower posyandu cadres and establish adolescent posyandu centers. The objective of this program is to create adolescent posyandu centers as platforms for promoting and educating about stunting prevention among adolescents. Methods employed include focus group discussions, socialization of adolescent posyandu concepts, training on adolescent posyandu management, and activity mentoring. The outcomes of this community service are: 1) a successful focus group discussion leading to the decision to establish a community-funded adolescent posyandu; 2) successful socialization of adolescent posyandu concepts and the election of its management; 3) training for the elected management on posyandu management; and 4) three months of continuous mentoring for adolescent posyandu activities. The output of this community service is the formation of an active and sustainable adolescent posyandu that conducts activities such as addressing adolescent anemia and providing education on early marriage to prevent stunting. In conclusion, the community service program has been successfully implemented, resulting in the establishment of an adolescent posyandu with 45 members which has been operating regularly for four months.